Scientific Competences in Children From Early Childhood - Carvajal-Sánchez, Paola Andrea (2023)
Introduction. This article presents a review of research and authors who approached the concepts of competence, creative thinking, and learning environments from different perspectives as axes in the development of research competencies. These concepts describe the factors that incur in the educational dynamics of the child population. Objective. To identify the existing relationship between skills, emotions, and learning environments as axes for developing creative and critical thinking in boys and girls. Analysis. For the study, a qualitative paradigm was used from a hermeneutical perspective, favoring the documentary study as a research strategy. Results. It is essential to start in early childhood the strengthening of scientific skills in coordination with the education of emotions. This dyad is essential for developing skills and competencies, not only cognitive and academic but also social. Learning environments must, on the one hand, promote direct contact with the objects of knowledge and, on the other, generate links; both elements potentiate being, knowing, and doing materialized in the development of scientific skills. Conclusions. The basic devices are activated while educational possibilities are generated, in which boys and girls can feel, touch, see, and smell. Likewise, this leads to the development of creative, scientific, and critical thinking.